2017
DOI: 10.1007/s00261-017-1329-7
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound (CEUS) of the abdominal vasculature

Abstract: Vascular diseases account for a significant proportion of abdominal pathology and represent a common referral source for abdominal ultrasonographic examinations. B-mode, color Doppler, and spectral Doppler analyses are well-established in the evaluation of abdominal blood vessels although they may occasionally be limited by lower sensitivity for slow flow visualization or the deeper location of abdominal vascular structures. The introduction of microbubbles as ultrasonographic contrast agents has rendered cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…CEUS advantage over conventional ultrasonography is its ability to examine the microvasculature, and recent studies have shown its higher sensitivity in the differential diagnosis of malignant vs benign portal vein thrombosis. Enhancement of thrombus during the arterial phase suggests malignant neovascularization …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CEUS advantage over conventional ultrasonography is its ability to examine the microvasculature, and recent studies have shown its higher sensitivity in the differential diagnosis of malignant vs benign portal vein thrombosis. Enhancement of thrombus during the arterial phase suggests malignant neovascularization …”
Section: Discussionmentioning
confidence: 99%
“…CT and MRI images have been reported, but ultrasonographic features are less well known, especially with contrast‐enhanced ultrasonography (CEUS). CEUS is a simple, fast, and safe imaging technique, which is useful to assess the nature of endoluminal lesions . Here, we report CEUS findings in a case of primary IVC leiomyosarcoma.…”
Section: Introductionmentioning
confidence: 92%
“…At the same time, CT can effectively show the blood supply of the nidus in patients. Therefore, the combination of the two methods can significantly improve the diagnostic accuracy of cystic renal cell carcinoma and help patients to receive timely treatment in order to reduce the damage caused by cystic renal cell carcinoma (26,27). Katabathina et al (28) considered that the diagnosis of malignancy degree of renal cystic lesion is particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…CEUS can diagnose endoleaks with higher accuracy than CTA and can be used to re-categorize previously diagnosed type V endoleaks (Figs. 8,9) [27,[64][65][66][67][68][69]. Detection of endoleaks with CEUS is typically performed through a qualitative assessment of enhancement, although quantitative analysis with TIC has also been considered, with promising results [27,28].…”
Section: Aortamentioning
confidence: 99%